A Community Activist, a Cultural Anthropologist, and an Archaeologist Walk into a Cemetery: Re-establishing Community Pride After a Jim Crow Atrocity. (1st September 2020) - Bailey, Eric; Ewen, Charles
ABSTRACT: In 1914, following the passage of Jim Crow segregation laws, over a dozen African American graves were exhumed from the primarily White Cedar Grove Cemetery in New Bern, North Carolina and reburied in the nearby Black Greenwood Cemetery. A century later, local community activists contacted anthropologists at East Carolina University to investigate the site of this atrocity. Archaeological work relocated the reburied remains and found them to be in such poor condition that the city elected to post signage commemorating this history rather than moving the graves yet again. The collaboration between the city and the university was able to produce an acceptable, if not perfect, solution to a potentially volatile problem.